Income Dynamics of Female Traders in Border Markets Post-Revitalization - Marce Sherly Kase; Margareta D. Pangastuti; Yani Aprilini; Desmon R. Manane (Journal of Management and Business Innovations, 2026)
Traditional Government-led revitalization of traditional markets is intended to bolster competitiveness and improve traders' financial well-being. However, empirical literature remains divided regarding the actual outcomes of these initiatives on trader income. This study investigates the impact of market revitalization on female traders at the Kefamenanu Old Market, while also evaluating how business capital, operational hours, and professional experience influence their earnings. Adopting a quantitative approach, this research utilized primary data gathered from 50 female merchants who were active prior to the revitalization program. The methodology involved observational data and surveys, analyzed through classical assumption tests, paired sample t-tests, and multiple linear regression. The results reveal a statistically significant income growth following the revitalization project (p=0.002), with average earnings rising from IDR 5,501,000 to IDR 6,307,000. Moreover, the data indicates that business capital, the number of hours worked, and business longevity are key drivers of income, accounting for 56% of the variance (R^2=0.560). These findings underscore that when market upgrades are coupled with sufficient capital, increased labor input, and accumulated experience, they effectively enhance both the revenue and economic resilience of female traders. Keywords: Business Capital, Female Traders, Length of Business, Market Revitalization, Traders' Income, Working Hours